Visions of the new world: photography in Kafka's Der Verschollene - Duttlinger, C (Blackwell Publishing, 2006)
Photography plays a central role in Franz Kafka's fictional travelogue Der Verschollene (1912-14), where it features as both explicit motif and implicit source material. Having never visited the United States, Kafka drew on genuine travel photographs as inspiration for his novel, assimilating them into his depiction of an imaginary America. While some scenes maintain the photographic stasis of their originals, others are animated to express the dynamism of modern life and the disorientation this can produce in the viewer's mind. Alongside such public travel photographs, however, Kafka also makes use of private pictures taken from his own family album. These traditional studio portraits act as models for the photographs featured within the plot, which illustrate the protagonist's continued attachment to his European origins. The latent sense of oppression inherent in these bourgeois portraits finds more brutal expression in the photographic source material which underles the novel's unfinished conclusion. In the Oklahoma theatre episode photographic scenes of assassination and lynching invade the narrative, undermining its images of modernity and progress. In its diverse manifestations (both literal and intertextual) photography in Der Verschollene establishes a link between traditional and modern forms of visuality, thereby illustrating the circular, regressive character of the protagonist's journey.